PERTUMBUHAN DAN HASIL DELAPAN GENOTIPE JAGUNG MANIS YANG DIBUDIDAYAKAN SECARA ORGANIK DI LAHAN RAWA LEBAK - Rimma Ita Hutasoit; Nanik Setyowati; Mohammad Chozin (BPFP Universitas Bengkulu, 2020)
[GROWTH AND YIELD OF EIGHT SWEET CORN GENOTIPE ORGANICALLY GROWN IN SWAMPLAND]. Sweet corn (Zea mays saccharata Sturt) has a greater advantage than feed corn because of its early maturity and the price is more expensive. Recently, the need for sweet corn is higher than its production. To overcome these problems, it is necessary to expand the planting area by utilizing sub-optimal land such as swamps of low fertility. Agricultural intensification can be carried out through the use of organic materials to meet nutrient needs for growth and yield of sweet corn. Determination of varieties suitable for planting in sub-optimal land is also an effort to increase the productivity of sweet corn in swampland. This study aims to determine the potential of sweet corn genotype for organically cultivated in swampland. The material used in this study consisted of seven sweet corn genotypes and one comparative variety planted in experimental plots based on a Randomized Completely Block Design (RCBD) with three replications. The variables evaluated in this study were the growth, development, yield, and yield components of sweet corn. The results showed that the 8 sweet corn genotypes tested had significantly different in plant height, number of leaves, number of rows of seeds per cob, and yields per plot. Caps 17 B x Caps 22 and Caps 3 x Caps 5 are genotypes that have better growth than the comparative variety. On the other hand, the yield and yield components of the comparative variety was higher among the other genotypes tested.